2021
DOI: 10.1186/s12978-021-01170-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health of adolescent Syrian refugee girls in Lebanon: a qualitative study of healthcare provider and educator perspectives

Abstract: Background Adolescent Syrian refugee girls in Lebanon are thought to experience a disproportionate risk of poor sexual and reproductive health, related in part to conflict and displacement. The purpose of this qualitative study was to explore healthcare provider and educator perceptions of the sexual and reproductive health determinants and care-seeking behaviors of this vulnerable population. The findings of the study will inform a health intervention that aims to reduce early marriage and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…16 The increased risk of maternal deaths among Syrian refugees in Lebanon indicate to differential vulnerabilities in this population in terms of inadequate access to health care, specifically antenatal, contraceptive, and postnatal services. 17 Lebanon has universal coverage of facility-based birth with skilled attendants and high utilization of antenatal care. 18 For the Syrian refugee population in Lebanon, coverage of skilled attendance at birth is reported to be 87%-91% 19 to 99.4%.…”
Section: Discussionmentioning
confidence: 99%
“…16 The increased risk of maternal deaths among Syrian refugees in Lebanon indicate to differential vulnerabilities in this population in terms of inadequate access to health care, specifically antenatal, contraceptive, and postnatal services. 17 Lebanon has universal coverage of facility-based birth with skilled attendants and high utilization of antenatal care. 18 For the Syrian refugee population in Lebanon, coverage of skilled attendance at birth is reported to be 87%-91% 19 to 99.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a number of sources has shown that early marriage is high among adolescent Syrian refugees in Lebanon and qualitative studies suggest an unmet need for SRH information and services in this community ( 7 , 17 ). An estimated 35% of 20–24-year-old Syrian women in Lebanon married prior to reaching 18 years of age, a figure that is higher as compared with pre-conflict Syria, though nationally representative data are lacking ( 28 , 29 , 35 , 38 ).…”
Section: Contextmentioning
confidence: 99%
“…Pregnancy is common among married Syrian girls, with one study demonstrating that 61% of married adolescent girls younger than 18 had experienced at least one pregnancy, while over two thirds of married Syrian refugee women ages 18–24 reported not using any form of contraception ( 39 ). Despite this need, cultural norms and gender roles generally restrict adolescent girls' accessibility to SRH information ( 7 , 17 ). These norms extend even to parent-child communication, with mothers in multiple settings throughout the MENA region expressing that cultural taboos and their own insufficient knowledge of these topics discourage them from participating in open discourse on SRH matters with their daughters ( 7 , 40 42 ).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations